Key Stakeholder Perspectives on the Potential Impact of COVID-19 on Human Trafficking for the Purpose of Labour Exploitation - Murphy, Muiread (Anti-Trafficking Review, 2023)
While human trafficking in its different forms has received growing recognition, currently there is an absence of research providing empirical evidence on the potential impact of COVID-19. COVID-19 and its related challenges provide a lens through which the vulnerability and complexities inherent in human trafficking can be further ascertained and analysed. This article explores challenges encountered by key stakeholders primarily operating in the field of countering human trafficking for the purpose of labour exploitation across Europe. These challenges are categorised as increased vulnerability to human trafficking for the purpose of labour exploitation; the impact on services and support; and limitations on professional duties. A qualitative method involving sixty-five semi-structured interviews was employed to capture the on-the-ground experiences of a diverse cohort of stakeholders active during the pandemic.